Is the hour-specific bilirubin nomogram suitable for predicting hyperbilirubinemia. - (:unkn) unknown (My University, 2008)
OBJECTIVE: To demonstrate the effectiveness of the hour-specific serum bilirubin nomogram, described by Bhutani et al, in predicting significant hyperbilirubinemia in term Turkish newborns. METHODS: A total of 217 healthy term newborns without signs of hemolysis were enrolled. Serum bilirubin levels were obtained at discharge and whenever visible jaundice was observed. According to the percentile-based hour specific bilirubin nomogram the babies were grouped into four categories (high, high/low, intermediate or low risk zone). All babies were followed up for hyperbilirubinemia and examined between 7 to 10 days of life and a bilirubin level was obtained when jaundice was observed. RESULTS: The mean predischarge bilirubin of cases was 9.71+/-3.4mg/dl. Thirty six patients (16.6%) received phototherapy while none of the cases had an exchange transfusion. The distribution of cases according to the high risk, intermediate, low/high, and low zones and the percentage of babies who received phototherapy were, 21(63.6%), 10(38.5%), 3(4.5%) and 2(2.2%), respectively. The risk of phototherapy decreased to 0.35 times for every increasing week of gestational age. Babies in the high intermediate and high risk zones were more likely to receive phototherapy (OR:24.5 and OR:83.6) CONCLUSION: The hour-specific serum bilirubin nomogram described by Bhutani et al. predicted clinically significant hyperbilirubinemia in Turkish term newborns.